FACTORS AFFECTING THE INTEREST RATE OF SECURITIES - Burkhanov Aktam Usmanovich (Scholar Express Journals, 2024)
The article investigates the factors affecting securities and their interest rates from a scientific and theoretical point of view. The role of state securities in the economy of Uzbekistan, including the volume of state securities placed on the open market, real and nominal interest rates, is analyzed. Also, the relationship between the percentage of the state securities being placed and the dealers expressing demand has been studied. Conclusions and proposals were prepared based on the factors affecting the percentage of state securities
Keywords: interest rate; securities; factor; banking system